Sinergi Implementasi K3 (ISO 45001:2018) Dan Beban Kerja: Pengaruhnya Terhadap Output Kinerja Karyawan - Rudi Wibowo; Abdul Majid; Faiz Wahidatul; Abdul Aziz (ECO-BUILD, 2025)
Performance refers to the results achieved by an individual, and it can be influenced by various factors, including the implementation of ISO 45001:2018 concerning Occupational Health and Safety (OHS) and workload levels. This study aims to explore the relationship between Occupational Health and Safety (OHS), workload, and employee performance in the Metering Department at PT Pertamina Hulu Mahakam. This research employs a quantitative method with a descriptive approach. The sampling technique used is total sampling, involving all 45 employees of the Metering Department as the population. Data analysis was conducted using multiple linear regression, classical assumption testing, and hypothesis testing with the assistance of SPSS version 26.The results of the study address all the proposed hypotheses, examining the influence of Occupational Health and Safety (OHS) on employee performance, the impact of workload on employee performance, and the combined effect of OHS and workload on performance within the Metering Department.